Metabolic Engineering of Saccharomyces cerevisiae for High-Level Friedelin via Genetic Manipulation - Gao, Hai-Yun; Zhao, Huan; Hu, Tian-Yuan; Jiang, Zhou-Qian; Xia, Meng; Zhang, Yi-Feng; Lu, Yun; Liu, Yuan; Yin, Yan; Chen, Xiao-Chao; Luo, Yun-Feng; Zhou, Jia-Wei; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Friedelin, the most rearranged pentacyclic triterpene, also exhibits remarkable pharmacological and anti-insect activities. In particular, celastrol with friedelin as the skeleton, which is derived from the medicinal plant Tripterygium wilfordii, is a promising drug due to its anticancer and antiobesity activities. Although a previous study achieved friedelin production using engineered Saccharomyces cerevisiae, strains capable of producing high-level friedelin have not been stably engineered. In this study, a combined strategy was employed with integration of endogenous pathway genes into the genome and knockout of inhibiting genes by CRISPR/Cas9 technology, which successfully engineered multiple strains. After introducing an efficient TwOSC1T502E, all strains with genetic integration (tHMG1, ERG1, ERG20, ERG9, POS5, or UPC2.1) showed a 3.0∼6.8-fold increase in friedelin production compared with strain BY4741. Through further double knockout of inhibiting genes, only strains GD1 and GD3 produced higher yields. Moreover, strains GQ1 and GQ3 with quadruple mutants (bts1; rox1; ypl062w; yjl064w) displayed similar increases. Finally, the dominant strain GQ1 with TwOSC1T502E was cultured in an optimized medium in shake flasks, and the final yield of friedelin reached 63.91 ± 2.45 mg/L, which was approximately 65-fold higher than that of the wild-type strain BY4741 and 229% higher than that in ordinary SD-His-Ura medium. It was the highest titer for friedelin production to date. Our work provides a good example for triterpenoid production in microbial cell factories and lays a solid foundation for the mining, pathway analysis, and efficient production of valuable triterpenoids with friedelin as the skeleton.